Prevalence of Iron Deficiency Anemia Among Preschool-Aged Children in Uasin-Gishu County, Kenya - Kosgei, Sheila C.; Were, Gertrude M.; Serrem, Charlotte; Osano, Odipo; Ayua, Emmanuel (African Journal of Nutrition and Dietetics, 2026)
Globally, approximately 40% of all preschool-aged children are affected by anaemia. Iron deficiency anaemia (IDA) is the most prevalent form of micronutrient deficiency and the leading cause of anaemia among children. In Kenya, the prevalence of IDA among these children is 25%. This study assessed the prevalence of IDA and its associated factors among preschool-aged children in urban, peri-urban, and rural areas of Uasin Gishu County, Kenya. Ethical approval and a research permit were granted by AMREF ESRC and NACOSTI, respectively. A cross-sectional survey design was used to identify 289 children using stratified sampling. Biochemical tests were assessed using the HemoCue Hb 201. Data was analyzed using STATA version 18. The prevalence of IDA was 48.4%. Most of the children suffering from IDA were from the age groups of 6-12 months (22.1%) and 48-59 months (21.4%). Children from married parents were less likely to have IDA, [Odds ratio (OR):4.53; 95%CI, p-value <0.01]. An increase in wealth was associated with a decreased risk of IDA [OR: 5.45 (95% CI, 1.18 to 5.125), p-value <0.01]. There was a significant relationship between dietary diversity and IDA, Tau (2, N = 289) = 0.0667, p-value = 0.0445. The predictors of IDA are multi-factorial, and thus, multi-sectoral interventions may be necessary to combat IDA. Due to the high prevalence of IDA, the government should consider prophylactic iron supplementation for susceptible children, especially children aged between 6-23 months.